2019
DOI: 10.29309/tpmj/2019.26.12.3049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of oral maternal hydration and intravenous infusions on Amniotic Fluid Index in third trimester isolated Oligohydramnios.

Abstract: Objectives: To compare oral maternal hydration and intravenous infusion in women with third trimester isolated oligohydramnios in terms of mean change in amniotic fluid. Study Design: This is a Comparative Study. Setting: The study was conducted in Department of Gynecology, Pakistan Institute of Medical Sciences, Islamabad. Period: Between 1st May, 2015 to 31st July, 2016. Material & Methods: One hundred and fourteen pregnant females with singleton pregnancy, beyond 28 weeks gestation and AFI < 5cm were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The typical increase in AFI was 87%±33.5. Kiran et al (17) also reported that the acute maternal IV hydration increased the amniotic fluid volume. Lorzadeh et al (18) found that maternal IV fluid therapy more significantly increased AFI when compared to oral therapy.…”
Section: Discussionmentioning
confidence: 95%
“…The typical increase in AFI was 87%±33.5. Kiran et al (17) also reported that the acute maternal IV hydration increased the amniotic fluid volume. Lorzadeh et al (18) found that maternal IV fluid therapy more significantly increased AFI when compared to oral therapy.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanism of the AFI change after maternal hydration and its duration is still unclear. Some studies suggest that the fetus can respond to AFI changes after maternal hydration ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the present maternal hydration significantly increased AFI in women with oligohydramnios. Kiran et al found acute maternal hydration to increase amniotic fluid volume [ 7 ]. In line with the present study, numerous studies have demonstrated the effectiveness of maternal hydration in treating oligohydramnios [ 8 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of oligohydramnios includes hospitalization, specialist consultation, bed rest, oral rehydration and intravenous (I/v) hydration [ 7 ]. The effects of oral and infusion fluid therapies on AFI have been differently reported in literature [ 8 ].…”
Section: Introductionmentioning
confidence: 99%